Prospects of Heart tissue Bioprinting for COVID-19 recovered patients with irreversible heart damage. - Akter, Fariya (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.